Respiratory system pocket book with android-based augmented reality technology - Jodion Siburian; Rini Rahma Dina; M. Erick Sanjaya; Dian Arisandy Eka Putra Sembiring; Jehlie Alaisa Marasigan Contreras (University of Muhammadiyah Malang, 2024)
Biology is an abstract, elusive science, one of which is respiratory material. It requires a media that can visualize objects on a two-dimensional book of biology to a three-dimensional one with a learning video. Research aims to develop, describe kal, and describe the teacher's assessment and student response to the results of the product developed. This research and development using model 4D consists of define, design, foresight, and develop ate. The result of this realization is the production of a medium of pocket books and apps downloaded on android smartphone platforms, able to present in real, tangible, three-dimensional objects to respiratory matter. The media was declared worthy by the validator of materials and media experts with an average rating score on final validation at 84.68% and 93.17%. Trials in the field as practical tests were obtained an assessment result from teachers by 85.36%, student responses of small groups and large groups are 86% and 83.65%. Also, it is also noted that a media pocket book and applications using this augmented reality technology are worthy to be used by students in studying the human respiratory system for grade 11th MIPA SMAN 1 Kota Jambi.